ПРОСТРАНСТВЕННЫЕ ХАРАКТЕРИСТИКИ РИТУАЛЬНЫХ ПРАКТИК В НАРОДНОЙ МЕДИЦИНЕ БЕЛОРУСОВ - Володина, Татьяна; Лобач, Владимир (Acta Neophilologica, 2007)
The authors of the article pay attention to the main elements of a natural and cultural landscape, which are the place for ritual cure or a virtual subject/locus of medical magic procedure. The most frequent spacial categories are „The Centre of the World” and „The Border”, and also lines of communication of artificial (a road) or natural (a river) character which combine all the parts of the universe structure. All of them are invariants of different parts of the indivisible model of the world. This system of the universe is especially functional in the context of symbolical-ritual (magic) methods of the Belarusian popular medicine because it gave a possibility to a person of the Tradition to restore the cosmic order (here it is health as one of its components) without leaving „the cultural field” (home, farmstead, village).